Usefulness, Ease of use and Shopping habit Influence Post Covid-19 Online Purchase Intention on Shopee - Nahla Uyunul; Bernadetta Diansepti Maharani; Putri Dwi Cahyani (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study aims to analyze the influence of Perceived Usefulness and Perceived Ease of Use on Post Covid-19 Online Purchase Intention by Shopping Habit during Covid-19 as a mediating variable. The study seeks to determine the extent to which these factors contribute to increasing Post Covid-19 Online Purchase Intentions in the millenial generation use the shopee. using a quantitative research approach is causal associative in nature with Statistical Package for the Social Science (SPSS) tools. This research was conducted on a population consisting of all millennials in Yogyakarta, with a sample of 140 randomly selected respondents. Data was collected through a Likert scale-based questionnaire. The research findings show that perceived usefulness, perceived ease of use, and shopping habits during covid-19 have a positive and significant effect on post covid-19 Online purchase Intention. Perceived usefulness has a positive and significant effect on Shopping Habit during Covid-19. However, there is a gap between theory and results, on the Perceived Ease Of Use variable which states that there is no relationship between the perceived ease of use variable and shopping habit during covid-19. This study strengthens the role of variables, especially perceived usefulness on post covid-19 online purchase intention, besides expanding the theory of perceived usefulness and expanding the theory of shopping habits during covid-19. This study argues that perceived ease of use affects online purchase intention. These findings contribute to the literature on the importance of making digital marketing strategies more effective in online marketplaces